2009
DOI: 10.1163/138855409x12465364602422
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the interactions of soil microbes and nematodes

Abstract: Six different soil food webs, assembled from a bacterium, a bacterial-feeding nematode, a fungus and a fungal-feeding nematode, were established in replicated laboratory microcosms. Glucose was supplied as the sole carbon source for the microbes. Biomasses of the organisms and the concentration of dissolved organic carbon (DOC) were measured ten times during 20 weeks. A discrete dynamic model based on the material flow between system components was fitted to the experimental data. Bacterial-based food chains w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 35 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Interestingly, Candidatus Xiphinematobacter , a known endosymbiont of the plant-parasitic nematode group, Xiphinema americanum , , was dominant in nematode samples planted with A. fistulosum . Perhaps bacterial communities, even resistomes, have a potential transfer pathway through a complex trophic delivery via the plant–bacteria–nematode food chain . Although our aim was to focus on the effect of surface microbes, endophytic bacteria cannot be completely left out due to inevitable wounds of leaves.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Candidatus Xiphinematobacter , a known endosymbiont of the plant-parasitic nematode group, Xiphinema americanum , , was dominant in nematode samples planted with A. fistulosum . Perhaps bacterial communities, even resistomes, have a potential transfer pathway through a complex trophic delivery via the plant–bacteria–nematode food chain . Although our aim was to focus on the effect of surface microbes, endophytic bacteria cannot be completely left out due to inevitable wounds of leaves.…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps bacterial communities, even resistomes, have a potential transfer pathway through a complex trophic delivery via the plant−bacteria−nematode food chain. 62 Although our aim was to focus on the effect of surface microbes, endophytic bacteria cannot be completely left out due to inevitable wounds of leaves. Soil and plant bacterial communities are selectively introduced into nematodes, forming the core bacterial taxa.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Decreased abundance of bacterivores was associated with increased abundance of FOC which in turn strongly inhibited the abundance of soil beneficial bacteria in disease areas (Neher, 2005;Quénéhervé, 2008). Nieminen (2009) observed that soil beneficial bacteria provided available food resources for nematodes of Cephalobidae and Rhabditidae reproduced themselves. However, the mean abundance of fungivores was 40.2% higher in the disease area than in the control area.…”
Section: Comparison Of Soil Nematode Communities Between Banana Wilt mentioning
confidence: 92%